Quizzz! As A Tool For Innovative Educational Gamification In Higher Education - Fitriah Handayani; Amina Intes; Guntur Arie Wibowo; Didik Cahyono; Budi Mardikawati (Journal Neosantara Hybrid Learning, 2024)
Quizizz is a very useful gamification tool for use in innovative education in higher education. By using quizizz, can help and interest students in learning. In addition, by using Quizizz, can increase creativity, and can help evaluate learning easily. This research was conducted with the aim of seeing how effective the use of Quizizz is in higher education. Because in fact, the Quizizz application is a game-based application, which can involve the participation of all students in playing in class. The method used by researchers in examining Quizizz as a Tool for Gamification of Innovative Education in Higher Education is to use quantitative methods. The data obtained by the researcher was obtained from the results of the distribution of questionnaires. The distribution of the questionnaire carried out by the researcher was done online by using the Google From software. The results of the data acquisition will also be tested again using the SPSS application. From the research results, it can be known that Quizizz is very useful to be used in innovative education in higher education. Innovative education can be interpreted as a skillful, critical, and creative education. Therefore, Quizizz is very appropriate to be used as an innovative educational gamification tool in higher education, because Quizizz can present different learning materials than previous learning materials. From this research, researchers can conclude that with Quizizz, it can enable teachers to identify material that has not been mastered by students, and can measure the level of skills that have been improved by students. In addition, the use of Quizizz as gamification in universities can also train students independently to learn, such as making questions, as well as other interesting games that will be used to learn.